2006
DOI: 10.1007/s10545-006-0444-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of a filter paper method potentially applicable to mass and high‐risk urinary screenings for Fabry disease

Abstract: Fabry disease is an X-linked lysosomal storage disorder of glycosphingolipid catabolism resulting from a deficiency of the enzyme alpha-galactosidase A, and leading to the progressive accumulation of one biomarker, globotriaosylceramide (Gb(3)), predominantly elevated in the urine of these patients. We have developed a technique for the analysis of total Gb(3) in urine samples collected on filter paper, using liquid chromatography-tandem mass spectrometry (LC-MS/MS) with a triple quadrupole instrument. Existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Urine or plasma Gb 3 concentrations have been used as biomarkers for diagnostic purposes and to follow the effect of specific therapies such as ERT. 1,2 In addition, the measurement of plasma Gb 3 concentration was used as a pharmacodynamic marker to demonstrate the biological activity of agalα in vivo. 20 For patients with elevated plasma or urine Gb 3 concentrations before treatment, ERT resulted in an initial drop in Gb 3 concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine or plasma Gb 3 concentrations have been used as biomarkers for diagnostic purposes and to follow the effect of specific therapies such as ERT. 1,2 In addition, the measurement of plasma Gb 3 concentration was used as a pharmacodynamic marker to demonstrate the biological activity of agalα in vivo. 20 For patients with elevated plasma or urine Gb 3 concentrations before treatment, ERT resulted in an initial drop in Gb 3 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Plasma Gb 3 concentration has been found to be consistently elevated in hemizygous males with classic Fabry disease but variably elevated in some variant hemizygous males with residual enzyme activity and in heterozygous females. 5,6 No evidence has been published supporting the use of plasma or urine Gb 3 concentrations as a biomarker for disease progression or response to treatment.…”
Section: Original Research Articlementioning
confidence: 99%
“…Gb 3 is clearly useful as a diagnostic marker for individual patients and probably for screening for the disease in populations of patients at risk (2,6,15,16). It can be used as an indicator of the metabolic effect of infused ␣-galactosidase A for ERT (17,18).…”
Section: What Do We Know?mentioning
confidence: 99%
“…In this study, we used the filter paper method suggested by C. Auray-Blais et al which has the following advantages 5 . First, contrary to existing Gb3 techniques, which are both time-and labor-intensive, this filter paper method eliminates the lipid extraction, glycolipid isolation, centrifugation and evaporation steps, while maintaining the sensitivity and efficiency.…”
Section: Discussionmentioning
confidence: 99%